Non-surgical Treatments of Esophageal Cancer - Seifi Makrani, Danial; Hasanzadeh, Hadi; Allahverdi Pourfallah, Tayyeb; Ghasemi, Arash; Jadidi, Majid (Archives of Advances in Biosciences, 2015)
Esophageal cancer is one of the most common malignancies with a growing occurrence. It presently ranks ninth among the most frequent cancers in the world and the sixth leading cause of death from cancer. For a variety of reasons, the mainstream of patients with esophageal cancer is actually not suitable for Esophagectomy. More than 50% have locally advanced unresectable or metastatic tumors at diagnosis. Other reasons which exclude Esophagectomy include old age, comorbidity or refusal by the patient. For more advanced stages of esophageal cancers, the basis of non-surgical treatment is chemotherapy (CT) or radiotherapy (RT), either alone or in combination as chemoradiotherapy (CRT). The purpose of this study is to summaries and judgmentally analyzes current non-surgical treatments. Although the best treatment for locally advanced esophageal cancer is still being debated, the use of neoadjuvant chemoradiotherapy has gained acceptance.